Analisis dan Penerapan Metode Fuzzy AHP-TOPSIS dalam Penentuan Mitra Industri Sebagai Tempat Praktek Kerja Lapangan - Veri Julianto; Hendrik Setyo Utomo; Herpendi Herpendi (Jurnal Ilmiah Informatika, 2020)
Field Work Practices are part of achieving the expected competencies in the educational process. The suitability of students to companies that serve as street vendors is something that is important to note. The weakness of the previous field work practices system was that there were still many students who were inaccurate in choosing a company or institution as a place for street vendors. This study aims to help determine industry partners in accordance with the competency achievements of each department. The method to be used in this research is Fuzzy Analytical Hierarchy Process (FAHP) in the process of determining the weight priority of each criterion and the TOPSIS method in carrying out the ranking process. The criteria used are the suitability of the department with the company's core (C1), company credibility (C2), and company commitment (C3). corporate environment (C4), and the facilities provided (C5). Each of these criteria consists of several sub criteria. The weights of the criteria obtained through the FAHP are Furthermore, the process of ranking 37 companies using the TOPSIS method obtained the highest preference value, namely 0.8157.